Numerical Simulation of Incompressible Turbulent Flow using Linear Eddy Viscosity-based Turbulence Models - Majumdar, Sekhar; Rajani, B.N.; Kulkarni, D.S.; Subrahmanya, M.B. (Defence Science Journal, 2010)
The present study focuses on the recent development of an implicit pressure-based finite volume algorithm for numerical solution of Reynolds averaged Navier-Stokes equations (RANS) in an inertial frame of reference for the prediction of unsteady incompressible flow problems. The algorithm uses boundary-conforming, multiblock structured grid with moving boundaries, collocated variable arrangement with momentum equations resolved along cartesian directions, second-order accurate spatial and temporal discretisation schemes for the convective fluxes and a pressure-velocity solution strategy. Effect of turbulence was simulated using appropriate linear eddy viscosity-based turbulence models. The capabilities and limitations of the cost-effective unsteady Reynolds averaged Navier-Stokes (URANS) approach has been demonstrated for few application problems of engineering interest. Defence Science Journal, 2010, 60(6), pp.614-627, DOI:http://dx.doi.org/10.14429/dsj.60.603